Mattering to God and to the Congregation: Gendered Effects in Mattering as a Mechanism Between Religiosity and Mental Health - Bonhag, Rebecca (Journal for the scientific study of religion, 2021)
A vast literature suggests favorable links between religiosity and mental health. Yet, the concept of “mattering” is an underexplored concept in the sociology of religion. Using a sample of U.S. adults from the 2017 Baylor Religion Survey, we investigate whether any associations between several aspects of religiosity (worship attendance, prayer, attachment to God, and God image) and mental health may be mediated by perceptions of mattering, and whether these pathways differ for men and women. Results from structural equation models indicate that mattering mediates the relationships between attachment to God, holding a judgmental God image, and worship attendance with depressive symptoms for women only. Further, holding a judgmental God image and worship attendance are mediated by mattering in predicting women's anxiety. We discuss the impact of mattering and the gendered pathways through which some aspects of religion and mental health are connected.